Hubungan antara Persepsi terhadap Harapan Orang Tua dengan Ketakutan akan Kegagalan Akademik pada Anak Sulung - Mutia Novillasari; Sayang Ajeng Mardhiyah (Universitas Muhammadiyah Jember, 2021)
This study aims to determine the relationship between perceptions of parents expectations with fear of academic failure in firstborn children. The research hypothesis is that there is a relationship between perceptions of expectations of parents and fear of academic failure in firstborn children.The subject of this research was 119 eldest children who were students at Sriwijaya University. The sampling technique in this study is by using a purposive sampling technique. The data collection method uses a scale of perceptions of parents' expectations and fear of academic failure, which refers to the dimensions of parents expectations from Sasikala and Karunanidhi (2011) and aspects of fear of failure from Conroy (2004).The results of the research hypothesis test showed a relationship between perceptions of parents' expectations and fears of academic failure with a positive correlation of 0,366 and significance of 0.000 (p 0.05). These results indicate a relationship between perceptions of parents' expectations and fears of academic failure, so the hypothesis in this study was accepted.